Kingdom of Lesotho : Poverty Reduction Strategy Paper: National Strategic Development Plan. (IMF Staff Country Reports; Country Report ;, 2012)
This paper describes the Kingdom of Lesotho's Poverty Reduction Strategy Paper and National Strategic Development Plan (NSDP) 2012/13-2016/17. NSDP recognizes, as a point of departure, the need and urgency for Lesotho to radically transform its economy. To achieve the National Vision goals and to reduce poverty and achieve sustainable development, the NSDP strategic goals will be to pursue high, shared, and employment-creating economic growth and develop key infrastructure. The mining investment of more than M 5 billion will lead to increased diamond exports, higher GDP, and faster growth in tax revenues.